Emulsifier and Highly Processed Food Intake and Biomarkers of Intestinal Permeability and inflammation in the Cancer Prevention Study-3 Diet Assessment Sub-Study. (29th May 2020) - Um, Caroline; Hodge, Rebecca; Gewirtz, Andrew; Stevens, Victoria; Jacobs, Eric; McCullough, Marjorie
Abstract: Objectives: Emulsifiers may increase intestinal permeability, inflammation, and colorectal carcinogenesis in animals. Highly processed foods are associated with obesity and may increase risk of chronic diseases, including cancer. We estimated intake of emulsifiers and highly processed foods in participants from the Cancer Prevention Study-3 Diet Assessment Sub-study and examined their association with biomarkers of gut permeability and inflammation. Methods: This study included 657 men and women who completed six 24-hr dietary recalls and two fasting blood samples over one year. Antibodies (IgG and IgA) to flagellin and lipopolysaccharide (LPS) and glycoprotein acetyls (GlycA) were measured using enzyme-linked immunosorbent assay and nuclear magnetic resonance, respectively. Total flagellin and LPS were each calculated as the sum of IgG and IgA; total antibody comprised the sum of total flagellin and LPS. Foods containing ≥1 emulsifier were identified from ingredient lists; foods typically containing emulsifiers were coded as such if an ingredient list was not available. We estimated emulsifier intake as 0.5% of total food weight, per FDA guidance. Highly processed foods were defined using the NOVA and Poti et al. classification systems and calculated as % grams of total foods and % kcal of total energy. Multivariable-adjusted generalized linear models were used to estimate associations of emulsifier and processed food quartiles with continuous antibody or inflammatory biomarkers. Results: Higher emulsifier intake (g/d) was not associated with total flagellin ( P -trend = 0.48), total LPS ( P -trend = 0.61), total antibody ( P -trend = 0.49), or GlycA ( P -trend = 0.16). Higher processed food intake (% kcal/d) was associated with higher total LPS ( P -trend = 0.001) and total antibody ( P -trend = 0.01) but not with other biomarkers, whereas processed food intake estimated as % g/d was only associated with higher GlycA ( P -trend = 0.02). Conclusions: Our results suggest highly processed food, but not emulsifier, intake may be associated with gut permeability biomarkers. Additional studies are needed to further understand the relationship between emulsifier and highly processed food intake and intestinal permeability and inflammation. Funding Sources: The American Cancer Society funds the creation, maintenance, and updating of the Cancer Prevention Study-3 cohort.